Roundtable discussion at the Fares Center, including Provost Jamshed Bharucha and Fletcher School professor Leila Fawaz. Photo 039 - Tobin, Joanie (Tufts Archival Research Center, 2008)
Roundtable discussion at the Fares Center, including Provost Jamshed Bharucha and Fletcher School professor Leila Fawaz.